Cardiomyocyte proliferation and progenitor cell recruitment underlie therapeutic regeneration after myocardial infarction in the adult mouse heart - Malliaras, Konstantinos (WILEY-VCH Verlag, 2013)
Cardiosphere-derived cells (CDCs) have been shown to regenerate infarcted myocardium in patients after myocardial infarction (MI). However, whether the cells of the newly formed myocardium originate from the proliferation of adult cardiomyocytes or from the differentiation of endogenous stem cells remains unknown. Using genetic fate mapping to mark resident myocytes in combination with long-term BrdU pulsing, we investigated the origins of postnatal cardiomyogenesis in the normal, infarcted and cell-treated adult mammalian heart. In the normal mouse heart, cardiomyocyte turnover occurs predominantly through proliferation of resident cardiomyocytes at a rate of ∼1.3–4%/year. After MI, new cardiomyocytes arise from both progenitors as well as pre-existing cardiomyocytes. Transplantation of CDCs upregulates host cardiomyocyte cycling and recruitment of endogenous progenitors, while boosting heart function and increasing viable myocardium. The observed phenomena cannot be explained by cardiomyocyte polyploidization, bi/multinucleation, cell fusion or DNA repair. Thus, CDCs induce myocardial regeneration by differentially upregulating two mechanisms of endogenous cell proliferation.